2014
DOI: 10.1590/s0102-33062014000200014
|View full text |Cite
|
Sign up to set email alerts
|

Phenology, caudex growth and age estimation of Cyathea corcovadensis (Raddi) Domin (Cyatheaceae) in a subtropical forest in southern Brazil

Abstract: Cyathea corcovadensis (Raddi) Domin occurs in northeastern, southeastern and southern Brazil, being widely distributed in the last. This was a three-year study, conducted from August 2008 to July 2011, in which we evaluated C. corcovadensis in a subtropical forest in southern Brazil. We also estimated the ages of the plants. Except in June and July of 2009, monthly leaf emergence and senescence were continuous and irregular, which prevented total leaf abscission, during that first year. Leaf emergence, senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…A tendency was observed for arborescent fern species that occur in the state of Rio Grande do Sul to produce spores during the hottest months with the longest days. Studies on the phenology of Dicksonia sellowiana (Schmitt et al 2009), C. atrovirens (Schmitt & Windisch 2012) and C. corcovadensis (Neumann et al 2014) found that the production of fertile leaves was related to an increase in the temperature and photoperiod. The fertile leaves obtained from the natural environment in which C. phalerata occurs were collected during the months under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A tendency was observed for arborescent fern species that occur in the state of Rio Grande do Sul to produce spores during the hottest months with the longest days. Studies on the phenology of Dicksonia sellowiana (Schmitt et al 2009), C. atrovirens (Schmitt & Windisch 2012) and C. corcovadensis (Neumann et al 2014) found that the production of fertile leaves was related to an increase in the temperature and photoperiod. The fertile leaves obtained from the natural environment in which C. phalerata occurs were collected during the months under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It is not unusual for some phenological events to be correlated with weather and not others because other extrinsic and intrinsic factors, such as soil temperature, photoperiod, and stored nutrients, may influence fern phenology (Odland 1995;Landi et al 2014;Neumann et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Little work on fern phenology has occurred in the subtropics, but 16 species in Taiwan showed varying phenological responses that were due primarily to precipitation (e.g., emergence of fertile leaves) or temperature (e.g., leaf emergence, expansion and mortality, and spore D r a f t 4 maturation and release; Lee et al 2009). Also, leaf emergence, senescence, and fertility of the tree fern Cyathea corcovadensis (Raddi) Domin were correlated, in part, with temperature in subtropical Brazil (Neumann et al 2014). Despite some evidence that phenology often responds to temperature and precipitation, not all phenological rhythms do (Tryon 1960;Moran 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Although, the ecological importance of tree ferns has been highlighted in the literature (Arens & Baracaldo 1998;Moran et al 2003;Schmitt & Windisch 2005;Fraga et al 2008;Medeiros & Aidar 2011), studies about this plant group are still scarce. In Brazil, most studies regarding tree ferns were conducted in the Atlantic Forest domain, focusing mainly on phenology (Schmitt & Windisch 2005;Schmitt et al 2009;Neumann et al 2014) and population structure (Mantovani 2004;Schmitt & Windisch 2007;Gasper et al 2011). Relationships among environmental variables and the distribution and population structure of ferns were investigated by Tuomisto et al (2019) in the Amazon; notwithstanding, the authors did not focus exclusively on tree ferns, but rather on all types of ferns.…”
Section: Introductionmentioning
confidence: 99%